Cooperation Between a Port and Local Community In Light of Sustainable Development - Marzi, Boris; Logožar, Klavdij (European Journal of Sustainable Development, 2019)
Ports represent the starting and ending point of maritime transport. Representing the meeting points of cargo exchange between maritime and other means of transport, they are an indispensable part of transport-logistic chain. Port also have an important role in development of the surrounding/hosting area from economic, social and environmental aspect. In order to operate successfully, a port must work and act in accordance with sustainability – environmentally, economically and socially responsible. The article presents a case study of sustainable coexistence between an economic subject – cargo port and its natural and social surrounding. Examples of port process and operations improvements in light of sustainable development and harmony with local community will be presented. Keywords: port system, local community, sustainable development